Direct anterior approach for total hip arthroplasty: Hip biomechanics and muscle activation during three walking tasks. (October 2021) - Ippolito, Giorgio; Serrao, Mariano; Conte, Carmela; Castiglia, Stefano Filippo; Rucco, Ferdinando; Bonacci, Enrico; Miscusi, Massimo; Pierelli, Francesco; Bini, Fabiano; Marinozzi, Franco; Zitiello, Michele; Ragona, Chiara; et al.
Abstract: Background: Total hip replacement with minimally invasive direct anterior approach using the "Smith Petersen" interval is an alternative technique to conventional surgery aimed at preserving the integrity of the muscles around the hip joint. This study aimed to observe hip biomechanics, gait variables, hip muscle activation and locomotor performance during three locomotor tasks (forward, lateral, and backward walking), in subjects who undergo total hip arthroplasty with direct anterior approach. Methods: Fourteen patients with primary osteoarthritis who underwent direct anterior approach were included in the study. The optoelectronic 3-D motion analysis system integrated with an electromyography surface device was used to acquire the biomechanics of patients before surgery and at 3 and 6 months post-surgery. Spatio-temporal, dynamic, and hip muscle electromyographic parameters were analyzed and compared whit those of healthy controls. Findings: Almost all gait parameters improved after surgery. The majority of gait variables neared to the control group at 6 months, while the hip joint range of motion did not. The abnormally increased activation of the muscles around the hip joint was reduced at 6 months post-surgery during all three locomotor tasks. Conversely, the altered gait phase-related electromyographic pattern did not change after the surgery. Interpretation: Our results indicate that hip and gait function during several locomotor tasks improved after surgery, while simultaneously either preserve or restore the muscle activation around the hip joint. A full biomechanical evaluation of the hip function during locomotion may aid physicians and surgeons in optimizing the management of patients before and after hip replacement surgery. Highlights: Patients after hip replacement obtain a series of gait function improvements. The majority of gait variables normalized in patients at 6 months post-surgery. The surgery reduce the hyperactivation of the hip muscles around the hip joint.